Addressing graft-versus-host disease in allogeneic cell-based immunotherapy for cancer - Zibai Lyu; Siyue Niu; Ying Fang; Yuning Chen; Yan-Ruide Li; Lili Yang (Experimental Hematology & Oncology)
Abstract Allogeneic cell-based immunotherapies, particularly CAR-T cell therapy, represent a significant advancement in cancer treatment, offering scalable and consistent alternatives to autologous therapies. However, their widespread use is limited by the risk of graft-versus-host disease (GvHD). This review provides a comprehensive overview of GvHD in the context of allogeneic cell-based cancer immunotherapy and evaluates current strategies to mitigate its effects. Key strategies include genetic engineering approaches such as T cell receptor (TCR) knockout (KO) and T cell receptor alpha constant (TRAC) CAR knock-in. Alternative immune cell types like natural killer (NK) cells and natural killer T (NKT) cells offer potential solutions due to their lower alloreactivity. Additionally, stem cell technology, utilizing induced pluripotent stem cells (iPSCs), enables standardized and scalable production of engineered CAR-T cells. Clinical trials evaluating these strategies, such as UCART19 and CTX110, demonstrate promising results in preventing GvHD while maintaining anti-tumor efficacy. The review also addresses manufacturing considerations for allogeneic cell products and the challenges in translating preclinical findings into clinical success. By addressing these challenges, allogeneic cell-based immunotherapy continues to advance, paving the way for more accessible, scalable, and effective cancer treatments.